Dynamic Changes in Myofibroblasts Affect the Carcinogenesis and Prognosis of Bladder Cancer Associated With Tumor Microenvironment Remodeling - Du, YiHeng; Sui, YiQun; Cao, Jin; Jiang, Xiang; Wang, Yi; Yu, Jiang; Wang, Bo; Wang, XiZhi; Xue, BoXin (Frontiers in Cell and Developmental Biology, 2022)
Bladder cancer (BLCA) is a tumor that possesses significant heterogeneity, and the tumor microenvironment (TME) plays an important role in the development of BLCA. The TME chiefly consists of tumor cells and tumor-infiltrating immune cells admixed with stromal components. Recent studies have revealed that stromal components, especially cancer-associated fibroblasts (CAFs), affect immune cell infiltration and modulate the extracellular matrix in the TME of BLCA, ultimately impacting the prognosis and therapeutic efficacy of BLCA. Among the subgroups of CAFs, myofibroblasts (myCAFs) were the most abundant and were demonstrated to play an essential role in affecting the prognosis of various tumors, including BLCA. However, the dynamic changes in myCAFs during carcinogenesis and tumor progression have been less discussed previously. With the help of bioinformatics algorithms, we discussed the roles of myCAFs in the carcinogenesis and prognosis of BLCA in this manuscript. Our study highlighted the pathogenesis of BLCA was accompanied by a decrease in the abundance of myCAFs, revealing potential protective properties of myCAFs in the carcinogenesis of BLCA. Meanwhile, the reduced expressions of myCAFs marker genes were highly accurate in predicting tumorigenesis. In contrast, we also demonstrated that myCAFs regulated extracellular matrix remodeling, tumor metabolism, cancer stemness, and oncological mutations, ultimately impacting the treatment responsiveness and prognosis of BLCA patients. Thus, our research revealed the bimodal roles of myCAFs in the development of BLCA, which may be associated with the temporal change of the TME. The in-depth study of myofibroblasts and the TME may provide potential diagnostic biomarkers and therapeutic targets for BLCA.